Investigation of the impact of compression garments on endurance running performance and exercise induced muscle damage in the lower leg - Geldenhuys, Alda Grethe (MRC/UCT RU for Exercise and Sport Medicine, 2018)
Introduction: Compression garments utilisation is very popular among runners despite the relative lack of consensus in the literature regarding a beneficial impact. Methods: A randomised controlled experimental study was conducted in healthy, uninjured endurance runners (n=41) participating in the Old Mutual Two Oceans 56km race. The experimental group (n=20) trained for six weeks and participated in the race wearing below knee compression garments while the control group (n=21) did not. Participants were tested on four occasions for various markers of exercise induced muscle damage (EIMD) and running performance. Six weeks prior to the race, ultrasound scans of the medial gastrocnemius, mid-calf and figure-of-8 ankle circumference baseline measurements were performed. Shortly prior to the race, these measurements were repeated in addition to a countermovement jump (CMJ) test. Immediately following the race, circumference measurements and CMJ testing were repeated in addition to pain ratings on the visual analogue scale (VAS). Race performance times were also obtained. Two days following the race, the ultrasound scans, circumference measurements and VAS pain ratings were repeated. Results: Ankle circumferences measurements increased significantly less (p=0.01, Cohen's d=0.9) in the experimental group from immediately after the race until two days post-race compared to the control group. There were no further statistically significant changes over time in any other objective outcome measure (i.e. mean mid-calf circumference, medial gastrocnemius mean muscle thickness and mean pennation angle, mean CMJ height and estimated peak power output nor in race performance) between the experimental and control groups. Selected pain ratings were statistically significantly worse in the experimental group. Muscle thickness and pennation angles were significantly greater in the control group compared to the experimental group two days following the race. Conclusion: There were limited indications of a beneficial impact of compression garments with minor improvements in ankle circumference measurements, but no further significant effects related to EIMD were detected. Furthermore, no ergogenic impact was detected. Based on the results of the study, there is limited evidence to support the continued utilisation of commercially available below knee compression garments during running.